Study of ionospheric topside variations based on NeQuick topside formulation and comparisons with the IRI-2012 model at equatorial latitude station, Chumphon, Thailand. Issue 2 (15th July 2017) - Jamjareegulgarn, Punyawi; Supnithi, Pornchai; Hozumi, Kornyanat; Tsugawa, Takuya
Abstract: It is well-known that the equatorial anomaly at equatorial and low latitudes is caused by the fountain effect, therefore, the modeling of topside electron density profiles (EDPs) and the knowledge of electron density distribution in the region are particular challenging. Chumphon station, Thailand, is located within this region. However, at this station, since only an FMCW ionosonde system is installed, the topside EDP cannot be automatically obtained. Therefore, in this work, the topside EDPs are derived using the NeQuick topside formulation of the NeQuick 2 model (namely, NeQuick-derived topside EDPs) and then compared with those of three options of the IRI-2012 model including NeQuick, IRI01-corr, and IRI2001 options. The results show that, at Chumphon station, the NeQuick-derived topside EDPs are generally closer to the topside EDPs of IRI01-corr option in winter season and the topside EDPs of NeQuick option in equinox and summer seasons. When analyzing the topside TEC values obtained from each profile and the IGS TEC, it is found that the topside TEC values integrated from NeQuick-derived topside EDPs and predicted by both IRI01-corr and IRI-2001 options of the IRI-2012 model are sometimes higher than the IGS TEC values observed at Chumphon. In addition, we study the diurnal variations of the scale height computed from NeQuick topside formulation ( Hsc ), hm F2 and fo F2 parameters. The correlation of Hsc with the parameters hm F2 and the bottomside thickness parameter of NeQuick model (B2bot ). The computed Hsc values during daytime are lower than those during nighttime and they show non-linear correlations with hm F2 and B2bot . The main cause of these discrepancies are possibly due to the B2bot expressions used to compute the Hsc .